The Intra-regional Divide in the Face of the Green Transition: Empirical Analysis for the Municipalities of Cantabria. - Alejandro Bedia-Carral; Marcos Fernández Gutiérrez; Ana Lara Gómez; Marina Gutiérrez (Revista de Economía Mundial)
The European Union is implementing an ambitious strategy to carry out a just green transition. Evidence shows, however, deep inter-regional differences in vulnerability to the green transition, which pose a risk for this strategy. This paper analyses intra-regional differences in vulnerability to the green transition, using data for the municipalities of a Spanish region: Cantabria. The results show a deep intra-regional divide, where deprived, rural and depopulated municipalities are the most vulnerable to the green transition. These results complement the existent evidence on inter-regional differences in vulnerability to the green transition in the European Union, extending it to the analysis of intra-regional differences. This shows that the green transition may increase polarisation not only between regions, but also within regions.